Characterization of the mitogenomes for two sympatric breeding species in Recurvirostridae (Charadriiformes) and their phylogenetic implications. Issue 1 (1st January 2017) - Yang, Chao; Wang, Qing-Xiong; Li, Xue-Juan; Xiao, Hong; Huang, Yuan
Abstract: Recurvirostridae is a family of Charadriiformes that displays an amazing amount of characterization at evolutionary level. The mitogenomes of Himantopus himantopus and Recurvirostra avosetta are 17, 378 bp and 16, 856 bp in size, respectively. Both two mitogenomes reveal the same gene order and genomic organization to that of typical avian mtDNA. The first conserved block with two interrupted poly-C and four long terminal repeats with 140 bp are present in H. himantopus control region. Phylogenetic analysis indicated that Recurvirostridae ( H. himantopus and R. avosetta ) has the closest relationship with Haematopodidae. We supported that Stercorariidea is a sister group to (Alcidae (Laridae, Sternidae)), and suggested that the status of Larus vegae should be further investigated.